Seroprevalence of infectious bronchitis virus in different types of chicken in Bangladesh - Bhuiyan, Zafar Ahmed; Giasuddin, Md; Khan, Zahed Uddin Mahmood (Asian Journal of Medical and Biological Research, 2018)
Infectious bronchitis virus (IBV) is a highly contagious viral disease of the chicken. It is possibly the most economically important viral respiratory disease of chicken after Avian Influenza and Newcastle disease. The virus also affects the female reproductive tract, causing poor quality of egg and loss of egg production. The study was conducted in four types of chicken (broiler, layer, sonali and Deshi) from 7 sub-districts under 4 districts of Bangladesh. Total 833 blood samples from 103 farms were collected and subjected to indirect ELISA test by commercially available IBV ELISA kits to detect specific antibodies against IBV. In overall 59.30% seroprevalence observed, 23.82% was found in broiler, 97.87% in layer, 71.83% in sonali and 83.46% in Deshi types of chickens. Broiler samples showed lowest seroprevalence with high CV (CV%=171.38), among them 76.18% were not seroconvert because of high maternal antibody or poor vaccine response. Layers showed highest seroprevalence with CV% 58.86 that is 18.00% chickens shows titer above 14000 which indicated field infection. Deshi chickens were not commercially vaccinated even though they had high seroprevalence rates 83.46% with mean titer 5333 and CV% 79.88, indicating that IBV is circulating as endemic diseases in the selected areas. Sonali chickens now reared as commercial chicken, have lower seroprevalence rates with mean titer 3160, CV% 128.39 indicating that these birds were not properly vaccinated as they required. To prevent the flocks from IBV, live and attenuated vaccination is required according to circulating strains. Asian J. Med. Biol. Res. March 2018, 4(1): 132-136